"Tazkirai Shuaro" - The Comparative Comments Of The Poets’ Number, Names And Sample Poems Of The Manuscripts And Publications - do’stova, surayyo (FILOLOGIYA UFQLARI JURNALI, 2022)
Although Hasanmurod Laffasi’s work "Tazkirai shuaro" has been used in several studies lso far, the textual differences between the existing manuscripts and the copies of the book, their causes, the role of the work in the history of literary criticism and editing, have not been thoroughly analysed. The views expressed in these tazlaras are of great signifrcance because of their reliability and proximity to history. In these aspects, it is essential to find copies of the TazkJrai shuaro manuscript, to identifu textual differencos between them, and at the same time to create the perfect text